An ocular lesion of unknown aetiology. Issue 2 (June 2021) - Drosslerova, Marie; Cernovska, Marketa; Vasakova, Martina; Havel, Libor
A 61-year-old Caucasian female patient presented to her general practitioner complaining of progressive diminished visual acuity, narrowed visual field and blurred vision in her right eye. She had a history of hepatic steatosis, arterial hypertension and bronchial asthma in childhood. She reported no alcohol abuse and was a former smoker (1 pack - year history of smoking, with more than 30 years smoke-free). Can you diagnose this patient with vision problems? https://bit.ly/3vGe5qy